The concept of al-istikhlaf and its importance in reclaiming the attributes of man as khalifah on earth - Wan Ismail, Wan Hibatul Hidayah; Berghout, Abdelaziz (ISTAC-IIUM Publication, 2024)
This paper examines the significance of the notion of al-Istikhlaf and its basic place in the Islamic worldview. One fundamental principle in the Islamic philosophy of life is the role and purpose of man as khalifah on earth. In the Islamic worldview, al-istikhlaf or vicegerency refers to the honorable responsibility and purpose that mankind willingly undertook. Being the khalifah on earth entails assuming responsibility for governing and overseeing the life of man within civilisations, and his development on earth in accordance with God's guidance and commands. This paper seeks to elucidate the imperative nature of regaining the notion of al-istikhlaf and employing it as a conceptual framework for the restoration and reconstruction of our vicegerent roles and responsibilities on earth. The paper uses textual analysis to examine various viewpoints and theories related to constructing the al-Istikhlaf narrative and re-introducing it prominently. The paper concluded that Al-Istikhlaf, an essential concept in Islam, has the potential to be expanded into an all-encompassing framework for analysing the challenges and problems encountered by man. It seeks to revisit the all-encompassing nature and attributes of man as khalifah and not a mere human animal. This paper proposes ongoing research on the alIstikhlaf framework and promoting it among scholars and researchers. The framework of Istikhlaf helps understand and articulate issues and problems facing contemporary man in a more integrated and ethically driven way.